Mundo pintoresco - JACKSON, W.M. editor (JACKSON, W.M., 1955)
Contenido : VIVIENDAS; ARGENTINA; ESCOCIA; CORAZON DEL AFRICA; LUGARES SAGRADOS DE LA INDIA; PASTORES; VENEZUELA; GALES; MESOPOTAMIA; DESIERTOS; JUDIOS; VENECIA; PERU; PIELES ROJAS; POLONIA; CAÑA DE AZUCAR; CONTINENTE ANTARTICO; JAMAICA